Computational modeling of flavor perception in complex food systems - Min Liu; Jinfeng Zhong; Xiong Liu; Pingping Shi; Xiaoli Qin (Journal of Food Engineering, 2027)

Ethyl cyclopentenolone suppresses browning in fresh-cut potatoes by regulating PPO activity, phenylpropanoid metabolism and antioxidant defense - Pingping Fan; Shaohe Jiao; Xiaoyong Chang; Xiongfeng Zhang; Junping Liu; Wei Liu; Lei Zhou (Postharvest Biology and Technology, 2026)

Non-linear responses and biocultural buffering of ancient tree multi-dimensional diversity along an urbanisation gradient - Pingping Tian; Yifu Liu; Wei Lyu; Yihao Dan (Landscape and Urban Planning, 2026)

Asynchronous recovery of hydrolytic and oxidative enzymes during wetland restoration - Xiangling Zhou; Ting Wang; Lifei Su; Siqi Zheng; Shijia Liu; Yi Liu; Wenhui Quan; Tingting Hu; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; et al. (Agriculture, Ecosystems & Environment, 2026)

Nanoconfinement-based advanced oxidation processes for water treatment - Pingping Zhao; Zhipeng Liu; Hengduo Xu; Shenwei Cheng; Zheng Wang; Yanqing Sheng (Journal of Environmental Chemical Engineering, 2026)

Inhibition of maltol on enzymatic browning in potato: Combined effects on PPO activity, substrate biosynthesis, and oxidative stress - Xiaoyong Chang; Pingping Fan; Zhaorui Liang; Xing Lu; Junping Liu; Wei Liu; Xiongfeng Zhang; Shaohe Jiao; Lei Zhou (Food Chemistry, 2026)

A charge and size-switchable Au2Pt nanosystem for deep-tumor penetration and combinatorial therapy of ocular uveal melanoma - Lingdan Kong; Linxin Chen; Pingping Huang; Linghong Wang; Kang Han; Xiaoqian Shi; Yue Zhang; Jizhen Wang; Yunhai Tu; Yuqin Wang; Yong Liu (Chemical Engineering Journal, 2026)

Cumulative damage analysis and experimental investigation of transmission tower structures under sequential seismic excitations - Pingping Nie; Haiqing Liu; Saiyu Shao; Zhiwen Yang; Jingrui Li; Siyi He (Soil Dynamics and Earthquake Engineering, 2026)

The Characterization and Antifungal Efficacy of NJ-62 Protein from Weizmannia coagulans CGMCC 9951 against Ceratocystis fimbriata - Jia Xu; Xiaohan Liu; Xin Li; Ying Wu; Pengyan Li; Shanshan Tie; Pingping Tian; Shaobin Gu (Probiotics and Antimicrobial Proteins, 2026)

Epigenetic Regulation of Gill Function in Japanese Flounder Under Hypoxic Stress Analyzed via Genome-Wide Methylome and Transcriptome Dynamics - Hengtai Tang; Chengnan Ding; Tianyang Cai; Guangling Li; Pingping Liu; Zhirui Zhang; Feng He (Journal of Ocean University of China, 2026)

Liraglutide affects mitochondrial function and histone acetylation through the NQO1/SIRT3 pathway in diabetic kidney disease - Jie Gao; Xiaoyu Lv; Pingping Zhao; Bingjing Pan; Jingfang Liu (Molecular and Cellular Biochemistry, 2026)

Nitroxoline attenuates sepsis-associated pancreatic injury through inhibiting NLRP3-inflammasome mediated pyroptosis - Tingzi Gong; Xiaohui Zeng; Cheng Li; Pingping Liu (Toxicology and Applied Pharmacology, 2026)

Magmatic differentiation of Paleoproterozoic carbonatites in the crust in North China Craton: Implications for rare earth element mineralization - Dongyang Liu; Cheng Xu; Marco Brenna; Zeng Lv; Pingping Liu (Precambrian Research, 2026)

Cooperative detoxification through GSTm1 and GSTs2 reveals distinct transcription factors BH1 and zen2 in dinotefuran resistance in Nilaparvata lugens - Bingjie Tang; Yutao Hu; Bin Liu; Xin Lei; Pingping Guo; Jiahui Liu; Wenqing Zhang (Pesticide Biochemistry and Physiology, 2026)

Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

Morphology, molecular identification, and pathogenicity of two Alternaria species associated with leaf spot of common bistort (Bistorta officinalis Delarbre) in China - Lin He; Jie Zhao; Jianxin Deng; Shanghua Liu; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Light engineering in aquaculture: physiological responses of Takifugu rubripes larvae to controlled LED irradiance - Xin Li; Songtao Liu; Yafang Liu; Pingping Wei; Yanling Wu; Yingying Fang; Fei Sun; Ying Liu; Yumeng Wu; He Ma (Frontiers in Marine Science, 2026)
Introduction While indoor aquaculture has expanded globally, optimal lighting strategies for fish growth remain understudied. This study aims to establish optimal LED protocols for indoor-reared Takifugu rubripes larvae. Methods T. rubripes larvae were maintained at 50, 250, 500, and 750 mW/m 2 (i50, i250, i500, i750) from hatching through 30 DPH. Growth, gene expression, and enzyme activities were measured. Results Positive growth effects were observed at i250 and i500 within 14–17 DPH, while i50 caused complete mortality after 21 DPH. At 20 DPH, i500 upregulated IGF-1 and BMP2 expression, whereas i50 downregulated BMP4 and SOX9. i50 elevated CTSF, IGM, and HSP70, indicating stress. LPS activity was highest in i250 at 15 DPH, while LDH was lowest in i50. From 10–20 DPH, AKP and ACP were consistently lower in i50. During 5–20 DPH, SOD was suppressed in i750, while T-AOC increased in i250. Discussion Light conditions critically modulate enzymatic activity and early growth in T. rubripes larvae, though underlying mechanisms require further investigation.

Responses of transcriptomic profile to cryopreservation in dwarf surfclam (Mulinia lateralis) sperm - Zhen Xu; Jing Wu; Zujing Yang; Xiaoting Huang; Lisui Bao; Pingping Liu; Xiaoxu Li; Yibing Liu (Cryobiology, 2026)

Hierarchical governance in biological invasion management: a signaling game framework - Haiyan Wang; Ming Liu; Sean Shao Wei Lam; Pingping Han (Environment, Development and Sustainability, 2026)

Subchronic exposure to decabromodiphenyl ethane impairs cognitive function and induces neuronal ferroptosis via disruption of mitochondria-associated endoplasmic reticulum membranes - Yuanteng Sun; Fei Xiong; Lingjie Wu; Zhihui Liu; Pingping Liu; Wenhao Li; Juan Zhang; Rongli Sun (Journal of Hazardous Materials, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Soil hydraulic pedotransfer functions for estimating saturated hydraulic conductivity: a deep symbolic regression approach with mean shift clustering - Cheng Zhang; Zhongwang Wei; Wei Shangguan; Fan Bai; Wenzong Dong; Qiyun Xiao; Hongwei Zhao; Pingping Liu; Qingliang Li; Yongjiu Dai (Journal of Hydrology, 2026)

Dermal absorption and percutaneous penetration of p-phenylenediamines (PPDs) and p-phenylenediamine quinones (PPD-Qs): Mechanisms and implications for human dermal exposure risks - Wenyan Wang; Yuhao Cao; Yizhen Wang; Pingping Wang; Bin Liu; Shaohan Zhang; Yumeng Shi; Hongkai Zhu; Lei Wang; Yarui Liu; Zhipeng Cheng (Journal of Hazardous Materials, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

Restoring aquaculture ponds to coastal wetlands using native vegetation reduces methane (CH4) production and emissions - Wenjing Liu; Hong Yang; Ping Yang; Qitao Xiao; Jujuan Gao; Lihua Wang; Chuan Tong; Yingzi Wang; Pingping Guo; Dongyao Sun; Yongxin Lin; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

A novel hybrid model for coastal aquaculture ponds integrating hierarchical decision-tree and ensemble-learning approaches from Sentinel satellites - Xiaoyan Yang; Jianqiang Wang; Jian Gao; Pingping Liu; Xingbai Hu; Fei Zhang; Chao Chen (Frontiers in Marine Science, 2026)
Coastal aquaculture ponds represent a significant contributor to economic growth and food provision, underscoring the necessity of precise spatial mapping to support sustainable resource management. Current extraction methods often rely on single-source data and are easily confused by spectral heterogeneity in complex coastal environments, leading to blurred boundaries and misclassification. To overcome these challenges, this study proposes an innovative hybrid model that combines multi-source feature stacking with a hierarchical decision-tree architecture for coarse extraction, followed by an ensemble-learning framework for fine-scale classification. Implemented on the Google Earth Engine cloud platform, the model integrates Sentinel-1 and Sentinel-2 data to leverage complementary spectral, microwave, and terrain features. Applied to the Zhoushan Archipelago in China, the approach produced a high-resolution distribution map of aquaculture ponds with clear boundaries and accurate geolocation. Compared with conventional approaches such as random forest (RF), classification regression trees (CART) and support vector machines (SVM), the proposed model achieved an overall accuracy of 87.34%, improving by 2.55% to 5.39%. The model also achieved a Kappa Coefficient of 73.82% and an F1 score of 89.46%, demonstrating its effectiveness and reliability for automated coastal aquaculture pond extraction in complex coastal environments.

Source Apportionment, Bioaccumulation, and Risk Assessment of Potentially Toxic Elements in Fish and Sediments from Urban Rivers: A Study in Chengdu - Shuhong Liu; Yaqin Yang; Pingping Wu; Junzhuo Cai; Zhang Cheng (Biological Trace Element Research, 2026)

Aliphatic Chain-Derived Fluorescein Aggregates for Surfactants Discrimination and CMC Determination - Pingping Zhou; Zhongshuang Hu; Wenfei Liu; Jing Ji (Journal of Fluorescence, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

An advanced decoupled polarimetric calibration method for the LuTan-1 hybrid- and quadrature-polarimetric modes - Lizhi Liu; Lijie Huang; Yidi Wang; Pingping Lu; Bo Li; Liang Li; Robert Wang; Yirong Wu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

From lunar terrain to learned representations: A comparative study of crater extraction - Ersa Wei; Xiangmei Liu; Minxuan Gao; Feng Zhang; Pingping Lu; Yanan Dang; Jiahan Wang; Tao Wu; Jiaqi Chen (Icarus, 2026)

Transcriptome Analysis Reveals the Mechanism by which Probiotic Alleviate the Response of Juvenile American Shad (Alosa sapidissima) to High Temperatures - Chuwen Qiu; Chubing Gao; Pingping Deng; Zhuo Sun; Yongshi Liu; Jiabo Xu; Yonghai Shi (Probiotics and Antimicrobial Proteins, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Cr-doped CeO2 enables wettability-matched Pt catalysts for nearly complete lignocellulose conversion - Pingping Lu; Weichao Chou; Jun Li; Nan Shi; Lunan Wu; Bin Lou; Jing Wu; Dong Liu (Journal of Environmental Chemical Engineering, 2026)

Reshaping metal composition and sources to reduce PM2.5 oxidative potential by clean energy policies in Xi'an, China - Lijing Zhang; Pingping Liu; Hongyu Yan; Yuhao Dong; Shaozhong Guo; Hongmei Xu (Atmospheric Environment, 2026)

Patent analysis of mRNA therapy using deep learning - Yuanqi Cai; Xuejing Zhang; Xiaoming Zhang; Jianxiong Ren; Pingping Wang; Jinyu Cong; Xiang Li; Huali Zuo; Benzheng Wei; Kunmeng Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of nitrogen, phosphorus, iron, and silicon on the growth, total lipid content, and fatty acid composition of the diatom Corethron sp. - Maoyingzang Peng; Pingping Liu; Ruibing Peng; Xiamin Jiang; Sheng Li; Maowang Jiang (Journal of Applied Phycology, 2026)

The impact of anti-gout medications on eight cardiovascular diseases: a Mendelian randomized study - Pingping Peng; Jingting Wang; Miaozhen Huang; Congting Hu; Suyan Liu; Jia Liu; Jiaqin Cai; Xiaoxia Wei; Hong Sun (European Journal of Clinical Pharmacology, 2026)

Group IIId ethylene responsive factor 34 as a positive modulator of ABA signal pathway in Arabidopsis - Li Zhang; Mingxin Piao; Luyao Ji; Zixun Gao; Pingping Wang; Zeng Zhou; Jinpeng Zou; Qingchi Shi; Fang Liu; Yuping Xie; Mingdi Bian; Zhenming Yang; et al. (Plant Science, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Persistent luminescent nanoparticle-based immunochromatographic assay integrated with a smartphone device for simultaneous detection of aflatoxin B1 and T-2 toxin - Aimei Zhang; Mingzhu Liu; Jingran Sun; Zunquan Zhao; Yonghui Wang; Xiaoli Li; Jin Wu; Yanjun Fang; Pingping Zhang; Jialei Bai (Food Chemistry, 2026)

A novel integrating quantitative and qualitative approaches for comprehensive assessment of wastewater: combined water quality and community attitudes - Fatima Fida; Pingping Luo; Misbah Fida; Shuangtao Wang; Irshad Hussain; Asim Khan; Liming Liu (Environmental Geochemistry and Health, 2026)

Rapid nitrogen removal in sandy beaches driven by periodic tidal inundations - Lin Wei; Pinghe Cai; Qingquan Hong; Tong Wu; Wei Liu; Yilin Cheng; Pingping Mi (Limnology and Oceanography, 2026)
Sandy beaches are an important passage for the transport of various forms of nitrogen from land to sea. However, export fluxes of these forms of nitrogen and the mechanisms controlling their transformation remain elusive. Using the 224 Ra/ 228 Th disequilibrium approach, we estimated export fluxes of dissolved inorganic carbon and dissolved inorganic nitrogen at three intertidal sandy beaches with distinct slopes along the southeast China's coast. We identified that sandy beaches are a hotspot of nitrogen loss in the coastal ecosystem, with nitrogen removal rates reaching up to 87.1 mmolN m −2 d −1 and removal efficiencies varying between 7% and 82%. Notably, nitrogen removal rates peaked at intermediate seawater percolation fluxes, reflecting the optimal balance of oxygen consumption, marine organic matter remineralization, and nitrate production for fueling denitrification in the beach's interior. In addition, total nitrogen removal increased with beach slopes. This is likely due to the fact that steeper beaches facilitate seawater to percolate more efficiently into the beach's interior and travel along a longer flow path before it drains out, thus allowing denitrification to prevail. Overall, our field observations reveal that instead of the surface “skin circulation,” the “body circulation” system within an intertidal beach governs fluid transport and solute exchange between land and sea. We conclude that intertidal sandy beaches function as an efficient biogeochemical reactor, which attenuates anthropogenic nitrogen inputs to the coastal ocean.

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Na₂CO₃-SiO₂-H₂O nanofluids synergistically treats coal dust and hydrogen sulfide - Chunming Ai; Chang Liu; Pingping Sun; Chao Liu (Journal of Environmental Chemical Engineering, 2025)

From hidden danger to rapid detection: silver-enhanced urchin-like tungsten oxide MEMS sensors for Listeria monocytogenes detection in refrigerated dairy - Xingyu Wang; Pingping Liu; Haijie Cai; Cheng Zhao; Weihao Wu; Haixia Zhou; Yayao Song; Zhaohuan Zhang; Yong Zhao; Yongheng Zhu (Food Chemistry, 2025)

Oligopeptide-loaded metal-organic framework nanocomposites promote regulatory T cell differentiation against periodontitis - Yu Wang; Xiaoqian Gong; Hongli Chen; Pingping Niu; Zhiduo Liu; Yao Sun (Chemical Engineering Journal, 2025)

Deformation Behavior of Deep Foundation Pit Enclosure Structures Adjacent to Operational Railways: Case Study from Hangzhou - Zhiang Liu; Pingping Rao; Jifei Cui; Donglong Xing (Geotechnical and Geological Engineering, 2025)

Characteristics and risk assessment of heavy metals and their acid-extractable fractions in atmospheric dustfall in urban and rural areas of Xi’an, China - Hao Zhang; Pingping Liu; Lijing Zhang; Shaozhong Guo; Hongyu Yan; Zhiwei Xue; Hongmei Xu; Zhenxing Shen (Air Quality, Atmosphere & Health, 2025)

Prediction of potential habitats of three Coptis species under climate change provides insights on their resource protection and cultivation across China - Pingping Lu; Jieru Chen; Hongting Liu; Xinyue Zhu; Zichun Ma; Xue Huang; Wei Zhang; Hezhong Jiang; Hai Liao; Jiayu Zhou (Environmental Monitoring and Assessment, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Seasonal dynamics of particulate organic matter sources in arid saline lakes: Insights from stable isotopes and Bayesian mixing models - Zulpiya Musa; Yonghong Liu; Xin Wang; Pingping Zhang; Min Cai; Shuqiong Kong; Hongchen Jiang (Journal of Environmental Management, 2025)

Bacterial necromass-derived organic matter triggers greenhouse gas production and priming effect in saline lake sediments - Jian Yang; Min Cai; Pingping Zhang; Mingxian Han; Hailong Liu; Haiyi Xiao; Jibin Han; Xiying Zhang; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2025)

Interfacial mechanisms regulating lipid digestion: a systematic study using Tween surfactants with varying structural features - Pingping Zhang; You Li; Zihao Wang; Yang Liu; Zhaoming Ran; Ying Cai; Baocai Xu; Ce Wang (Food Chemistry, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

A graded E-shaped piezoelectric energy harvester for ultra-broadband and high-capability energy harvesting - Pingping Liu; Hongjun Xiang; Bao Zhao (Engineering Structures, 2025)

Biotransformation of per- and polyfluoroalkyl substances (PFAS) in organisms - Yanhui Dai; Dina Ding; Minggao Cui; Pingping Duan; Yinglin Liu; Xia Liu; Tongtao Yue; Jian Zhao; Zhenyu Wang; Baoshan Xing (Chemical Engineering Journal, 2025)

Spatial metabolomics reveals the effects of Acanthopanax senticosus on region-specific alterations in neurotransmitters and metabolites levels in the brains of α-syn transgenic Parkinson’s disease model mice - Qi Zheng; Yi Lu; Donghua Yu; Liangyou Zhao; Yu Wang; Pingping Chen; Fang Lu; Shumin Liu (Metabolic Brain Disease, 2025)

The effect of vessel noise on behavior and physiology of orange-spotted grouper (Epinephelus coioides) under conditions with and without artificial lighting - Hui Liu; Zijian Lu; Pingping Shen; Kaicheng Zhang; Geng Qin; Jianping Yin; Qiang Lin; Huixian Zhang (Marine Pollution Bulletin, 2025)

Accumulation, biotransformation and time-dependent transcriptomic responses to PSTs in scallop kidneys - Moli Li; Lingling Kong; Xiaogang Xun; Liang Zhao; Lirong Chang; Huizhen Wang; Zhenmin Bao; Xiaoli Hu; Pingping Liu (Marine Pollution Bulletin, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

Multifunctional double-network hydrogel with enhanced interface engineering for high-performance flexible zinc-air batteries - Pingping Xu; Quanchao Zhang; Xingyu Chen; Jie Liu; Naiqin Zhao; Wenbin Hu; Cheng Zhong (Chemical Engineering Journal, 2025)

An ultrastable tetraazacalix[2]arene[2]triazine functionalized MXene for highly selective and sensitive determination of p-Phenylenediamines and their quinone derivatives in environmental water via HPLC-MS/MS - Yichan Huo; Xiong Wang; Yang Yi; Zhirong Yang; Wenchang Wang; Huaijie Yao; Pingping Liu; Wenfen Zhang; Shusheng Zhang (Chemical Engineering Journal, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Flower-like Ag/MIL-125-Ti/CoAl-LDH S-scheme heterojunctions toward optimized photothermal-photocatalytic performance - Yuankang Yao; Yi Yang; Zibin Wang; Pingping Liu; Zipeng Xing; Zhenzi Li; Wei Zhou (Chemical Engineering Journal, 2025)

Curcumin-based antibacterial waterborne polyurethane/gelatin composite film for pork preservation and freshness indication - Yuye Zhong; Zhenhong Zhang; Zhengjie Chen; Wenshuo Zhang; Xinghai Liu; Pingping Zhao; Tao Zhang; Houbin Li (Chemical Engineering Journal, 2025)

Single cell transcription revealing key transcription factors in embryonic kidney development - Jingxian Huang; Bing Yan; Hongwei Wu; Hougang Yang; Shaodong Luan; Haiyan Yu; Wei Shi; Pingping Ye; Fang Yuan; Qiang Yan; Fanna Liu; Lianghong Yin; et al. (Molecular and Cellular Biochemistry, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

A conformal regressor for predicting negative conversion time of Omicron patients - Pingping Wang; Shenjing Wu; Mei Tian; Kunmeng Liu; Jinyu Cong; Wei Zhang; Benzheng Wei (Medical & Biological Engineering & Computing, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Knock Off 3 SlNAIP Genes with Modified CRISPR-Cas9 Causes Dwarf Phenotype in Tomato - Jia Liu; Xinya Dan; Lili Wu; Pingping Fang; Yan Zhang; Xifeng Li; Yanfei Ding (Journal of Plant Biology, 2025)

Unexpectedly stable soil organic carbon in tidal marshes under combined nitrogen loading and increased inundation compared to individual effects - Tianning Fan; Jiafang Huang; Guopeng Liang; Shengen Liu; Dehong Hu; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo; Chuan Tong (Limnology and Oceanography, 2025)
Tidal marshes serve as critical carbon (C) sinks, yet face increasing threats from global environmental changes. While previous research has documented how nitrogen (N) loading and sea‐level rise affect total C pools individually, their impacts on soil organic carbon (SOC) stabilization remain critically underexplored, particularly when these factors co‐occur in tidal marsh ecosystems. Through a 3‐yr field experiment, we analyzed how these factors, alone and combined, impact SOC stabilization by examining SOC fraction dynamics. Results showed that N loading increased particulate organic carbon (POC) by 18% and decreased mineral‐associated organic carbon (MAOC) by 13%, reducing SOC stabilization. Conversely, increased inundation raised MAOC by 31% and decreased POC by 19%, promoting SOC stabilization. The decreased MAOC under N loading stemmed from reduced fungal necromass C, while the increased POC related to lower phenol oxidase activity. In contrast, with increased inundation, MAOC rose due to iron‐bound organic C (Fe‐OC) accumulation, while POC declined from increased phenol oxidase activity. When both factors were applied together, SOC stabilization remained at control levels. This occurred because the combined effect maintained oxidative enzyme activities and thus retained POC levels. The simultaneous reduction in fungal necromass C and enhancement of Fe‐OC associations established complementary mechanisms that maintained MAOC at levels equivalent to control. Our findings reveal that N loading and increased inundation drive contrasting patterns of SOC stabilization, while their combination produces uniquely stabilized C dynamics. This insight challenges single‐factor predictions and underscores the importance of multi‐factor experiments in understanding ecosystem responses under concurrent global change scenarios.

Divergence of microbial carbon use efficiency and soil organic carbon along a tidal flooding gradient in a subtropical coastal wetland - Ji Tan; Jiafang Huang; Wenhui Quan; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo (Water Research, 2025)

A heterogeneous sparsity knowledge guided evolutionary algorithm for sparse large-scale multiobjective optimization - Jing Jiang; Huoyuan Wang; Pingping Tong; Juanjuan Hong; Zhe Liu; Xing Zhuang; Benyue Su; Fei Han (Swarm and Evolutionary Computation, 2025)

Salcastaniols A-G, seven undescribed diterpenoids with cholinesterase inhibitory activities from Salvia castanea Diels f. tomentosa Stib - Zhaoyue Dong; Pingping Wang; Qingju Liu; Feng Ju; Miaomiao Sun; Mohammad Mahmoud Nagdy; Fancheng Meng; Guowei Wang; Zhihua Liao; Min Chen (Phytochemistry, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Unveiling the Characteristics of Microbiota in Different Mucosal Layers of Leopard Coral Grouper (Plectropomus leopardus) - Jiahui Wang; Shengtao Gao; Zhenyuan Xu; Zhihui Yang; Qianqian Mu; Zijian Li; Pingping Liu; Jingjie Hu; Zhenmin Bao (Marine Biotechnology, 2025)

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

Soil salinity accumulation and groundwater degradation due to overexploitation over recent 40-year period in Yaoba Oasis, China - Ting Lu; Pingping Luo; Jucui Wang; Yudong Lu; Aidi Huo; Liming Liu (Soil and Tillage Research, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Development and evaluation of high-throughput HD-Marker arrays in pacific white shrimp (Litopenaeus vannamei) - Mingyang Liu; Zhihui Yang; Xin Huang; Qifan Zeng; Qianqian Mu; Zhenyuan Xu; Zijian Li; Pingping Liu; Shi Wang; Jingjie Hu; Zhenmin Bao (Aquaculture, 2025)

Identification of Dufulin photolysis and hydrolysis products in water using a 13C stable isotope assisted HPLC-HRMS strategy - Bochi Yu; Yanli Man; Gabriel Sigmund; Pingping Wang; Jun Xie; Wei Wang; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu (Water Research, 2025)

Trees show higher resilience than herbs under phosphorus deficit induced by 12‐year simulated acid rain - Guangcan Yu; Mianhai Zheng; Ying‐Ping Wang; Mengxiao Yu; Jun Jiang; Enqing Hou; Nannan Cao; Shu Ye; Songjia Chen; Jingtao Wu; Fengcai Liu; Linhua Wang; et al. (Ecology, 2025)
Acid rain, with 60% deposition in Asia, may exacerbate plant phosphorus (P) limitation; however, its long‐term effects on different plant life‐forms remain largely undetermined. Understanding these effects is essential for predicting ecosystem resilience and promoting forest health under environmental change. Herein, we investigated the P status in two tree and two herb species and their rhizosphere soils after 12 years of acid treatment at three pH levels (pH: 4.0, 3.5, and 3.0) in a tropical forest in Southern China. We found that leaf, litter, and root P; leaf N and P resorption efficiency; and their ratios remained stable in trees; however, herb leaf and litter P levels declined. Acid addition reduced inorganic P in tree rhizosphere soil and inorganic and organic P in herb rhizosphere soil. Rhizosphere soil P fractions were more regulated by soil physicochemical properties and less regulated by microbial community in trees than in herbs. Under long‐term simulated acid rain, stable tree P status benefited from soil inorganic P depletion, and herbs partially met their P requirements via biological mineralization of soil organic P. These distinct P‐associated responses and acquisition strategies provide insights into safeguarding forest health among plants of different functional types under long‐term acid rain events.

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “Source and bioavailability of quaternary ammonium compounds (QACs) in dust: implications for nationwide exposure in China” [J Hazard Mater 480 (2024) 136268] - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2025)

Conversion of agricultural waste biomass resource into high-added-value composite and its potential for boosting synergistic removal of ammonia nitrogen in practical water - Junjie Yuan; Yao Zhu; Jizhang Wang; Zhigang Liu; Tao Zhang; Pingping Li; Fengxian Qiu (Food and Bioproducts Processing, 2025)

Degradation of TeCG catalyzed by graphene quantum Dot-reconstituted magnetic hydrotalcite composites - Yan Huang; Guangda Mu; Weiwei Huan; Yuxiang Yang; Hongmin Yuan; Irum Batool; Pingping Yao; Chengyin Wang; Xiangnong Liu; Chaoying Ni (Chemical Engineering Journal, 2025)

Fe, N-CQDs triggered the fabrication of alginate encapsulated g-C3N4 hydrogel for efficient photocatalytic activation of PMS and antibiotic degradation - Haiyan Yang; Xiao Cao; Yiyang He; Xinchao Zhang; Pingping Zhang; Xin Wang; Yuehong Liu; Suyun Xu; Yuyin Fang; Lin Gu (Carbohydrate Polymers, 2025)

Improving global soil moisture prediction based on Meta-Learning model leveraging Köppen-Geiger climate classification - Qingliang Li; Xiaochun Jin; Cheng Zhang; Wei Shangguan; Zhongwang Wei; Lu Li; Pingping Liu; Yongjiu Dai (CATENA, 2025)

How to encourage well-being with reminders interventions: A field experiment on food waste separation and composting behaviors - Zhu Mao; Buxin Han; Chuanbin Zhou; Pingping Liu (Waste Management, 2025)

Optimizing Strategy for Whole-Genome Genotype Imputation in Scallops - Yujue Wang; Ruixing Yao; Liang Zhao; Qianqian Zhang; Moli Li; Xiangfu Kong; Pingping Liu; Shanhuan Huang; Chen Hu; Zhenmin Bao; Xiaoli Hu (Aquaculture, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Treatment of sludge hydrothermal carbonization wastewater by ferrous/sodium percarbonate system: Effect of wastewater composition and role of coagulation and oxidation - Liming Liu; Luna Zhao; Shiyun Jin; Wei Zou; Hongxia Wang; Yu Xie; Changlan Hou; Yunbo Zhai; Pingping Luo (Water Research, 2024)

Response characteristics of soil Cd availability to microbes in paddy soil with long-term fertilization and its impact on Cd uptake in rice - Shuai Yuan; Pingping Chen; Wenxin Zhou; Hongmei Liu; Kaikai Cheng; Xiaoping Xiao; Haiming Tang; Zhenxie Yi (Science of The Total Environment, 2024)

Assessing the impact of various irrigation technologies on agricultural production: A water-energy‑carbon nexus perspective - Sifu Liu; Simeng Cui; Jan F. Adamowski; Nan Wu; Mengyang Wu; Pingping Zhang; Xinchun Cao (Science of The Total Environment, 2024)

Source and bioavailability of quaternary ammonium compounds (QACs) in dust: Implications for Nationwide Exposure in China - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2024)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Independent induction of calluses and nematophytes from exfronds and their potential application for kelp cultivation and germplasm conservation - Pingping Tian; Weiwei Wang; Yan Li; Guangjin Liang; Juan Sun; Yanling Liu; Guanpin Yang; Xiaojie Li (Journal of Applied Phycology, 2024)

PI3KR1 and AKT1 in largemouth bass (Micropterus salmoides): molecular cloning, characterization, and its involvement in the alleviation of hepatic glycogen deposition caused by insulin inclusion in vitro - Yuru Li; Shiwen Chen; Yijun Liu; Pingping Liu; Songlin Li; Ning Liu (Fish Physiology and Biochemistry, 2024)

Microvesicle-eluting nano-engineered implants influence inflammatory response of keratinocytes - Anjana Jayasree; Chun Liu; Carlos Salomon; Sašo Ivanovski; Karan Gulati; Pingping Han (Drug Delivery and Translational Research, 2024)
Besides enhancing osseo- and soft tissue integration, modulating inflammation at the implant site is also crucial for dental implant success. Uncontrolled peri-implant inflammation can cause significant loss of surrounding tissue and implant failure. It was recently shown that microvesicles (MVs), a less-studied type of extracellular vesicles, play a crucial role in cell-to-cell communication and may modulate angiogenesis and inflammatory response. The effect of MVs on regulating inflammation at an implant site, however, remains unexplored. In the current study, MVs were isolated and characterised from human primary gingival fibroblasts (hGFs) and loaded within titania nanotubes (TNTs, fabricated via anodisation on 3D Ti wire implants) towards their local release. The modified implants were characterised using SEM and confocal imaging to confirm the loading and local release of MVs from TNTs. In vitro studies demonstrated the internalisation of hGFs-MVs by human gingival keratinocytes (OKF6/TERT2 cell line), which caused a significant reduction in the production of pro-inflammatory cytokines. The results support MVs-releasing TNTs as a promising implant surface modification strategy to reduce inflammation, paving the way for further advancements in therapeutic dental implants. Graphical abstract

Satellite navigation signal quality monitoring algorithm based on DBO-SVM - Ershen Wang; Yilin He; Tengli Yu; Liang Liu; Song Xu; Pingping Qu; Tao Pang (Advances in Space Research, 2024)

Photobacterium pectinilyticum sp. nov., a novel bacterium isolated from surface seawater of Qingdao offshore - Yunqi Ding; Pingping Zhang; Yi Liu; Mei Liu; Yaru Wang; Ronghua Liu; Shuxian Yu; Xiao-Hua Zhang; Xiaolei Wang (Antonie van Leeuwenhoek, 2024)

The Chinese version of the Ohkuma questionnaire: reliability analysis and diagnostic value - Zhang Pingping; Lu Dezhi; Li Tingting; Zhang Hui; Liu huan; Wang Xiaowen; Liu Wenbo (Acta Neurologica Belgica, 2024)

Exploring influential factors on biomass and diversity of ancient trees in human-dominated regions: A case study in Guangdong Province, China - Pingping Tian; Yifu Liu; Wei Lyu; Hongcheng Wang (Journal of Cleaner Production, 2024)

Pioneer plants promote soil formation in a mixture of bauxite tailings and red mud - Xusheng Jiang; Mengting Lin; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu (Journal of Environmental Management, 2024)

The analysis of the overall failure of practical Zn−Ni battery - Pingping Xu; Quanchao Zhang; Jie Liu; Wenbin Hu; Cheng Zhong (Chemical Engineering Journal, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

The general patterns of water flow in loess slope system and implications for slope geological security - Li Feng; Maosheng Zhang; Hao Liu; Bin Zhang; Zhen Du; Pingping Sun; Junbo Bi; Liang Wang; Tianfeng Gu (Science of The Total Environment, 2024)

A novel quantity assessment of landscape ecological risk using human-nature driving mechanism for sustainable society - Lili Liu; Jiabin Wei; Pingping Luo; Yixuan Zhang; Yihe Wang; Ahmed Elbeltagi; Mohd Remy Rozainy Mohd Arif Zainol (Science of The Total Environment, 2024)

Performance of loach to reduce clogging matter in vertical-flow constructed wetlands: Hydraulic evaluation and metabolic processes - Xiuzheng Fu; Fanlong Kong; Pingping Duan; Fanyi Li; Wenxuan Hu; Xiaomin Liu; Zhengda Yu; Yuqian Cui (Chemical Engineering Journal, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Coastal conversion alters topsoil carbon, nitrogen and phosphorus stocks and stoichiometric balances in subtropical coastal wetlands - Minjie Hu; Jingtao Wang; Jordi Sardans; Hui Wu; Ranxu Ni; Pingping Guo; Ruibing Yan; Haoyu Liao; Chunya Liu; Josep Peñuelas; Chuan Tong (Science of The Total Environment, 2024)

Unravelling the structure-performance relationship of zeolite Beta in the catalytic cracking of low-density polyethylene by proposing gasoline factor as the descriptor - Yi Wang; Hao Wu; Yuanhao Liu; Wansheng Wang; Pingping Wu; Hongchao Fan; Zhihui Liu; Peng Bai; Zifeng Yan (Fuel, 2024)

Bioinspired PEDOT:PSS-PVDF(HFP) flexible sensor for machine-learning-assisted multimodal recognition - Pingping Wu; Lin Li; Songtao Shao; Junchao Liu; Jingxia Wang (Chemical Engineering Journal, 2024)

U(VI) sorption by CTAB/Bent–MOF-74 from various carbonate solutions - BingTao Gui; Jun Liu; Cheng Wang; Shilong Shi; Junxiang Shu; PingPing Ding; Juan Zhai; Changsong Zhao (Journal of Water Process Engineering, 2024)

One–third substitution of nitrogen with cow manure or biochar greatly reduced N2O emission and carbon footprint in saline–alkali soils - Sheng Zhang; Lihua Xue; Ji Liu; Pingping Jia; Ying Feng; Yi Xu; Zhijie Li; Xiaoning Zhao (Field Crops Research, 2024)

Stability Analysis of Unsaturated Soil Pit Under Vehicle Load - Pingping Rao; Junjie Meng; Jifei Cui; Weikang Feng; Sanjay Nimbalkar; Zhiang Liu (Geotechnical and Geological Engineering, 2024)

A novel yeast-based biosensor for the quick determination of Deoxynivalenol - Han Yang; Lianqun Du; Lu Geng; Xiao Liu; Zehua Xu; Ruonan Liu; Wentao Liu; Hu Zuo; Zongfen Chen; Xinyang Wang; Pingping Zhang; Tieqiang Sun (Analytica Chimica Acta, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Rotation of Celosia argentea and Sedum plumbizincicola promotes Cd phytoextraction efficiency - Jie Liu; Xusheng Jiang; Xuehong Zhang; Pingping Jiang; Guo Yu (Journal of Hazardous Materials, 2024)

Evolution of an arid social-ecosystem with different water utilization spanning 12,000 years - Aidi Huo; Zhixin Zhao; Pingping Luo; Qi Liu; Qiangbing Huang; Zhenhong Wang; Jianbing Peng (Journal of Cleaner Production, 2024)

Association Between Circulating Zinc Levels and Risk Factors of Metabolic Syndrome: Insights from a Bi-directional Mendelian Randomization Analysis and Cross-Sectional Study - Yuanyuan Wu; Guoqiong Xu; Ruixue Bai; Pingping Yu; Zhongxiang He; Mengxue Chen; Yukun Hu; Tao Jiang; Yuanhang Yang; Dongfang Liu; Ying Mei; Xiaoya Qi; et al. (Biological Trace Element Research, 2024)

Biochar application reduced carbon footprint of maize production in the saline−alkali soils - Sheng Zhang; Lihua Xue; Ji Liu; Longlong Xia; Pingping Jia; Ying Feng; Xingming Hao; Xiaoning Zhao (Agriculture, Ecosystems & Environment, 2024)

miR397 regulates cadmium stress response by coordinating lignin polymerization in the root exodermis in Kandelia obovata - Chenglang Pan; Mingxiong Zhang; Jianming Chen; Haoliang Lu; Xuemei Zhao; Xiaofeng Chen; Lu Wang; Pingping Guo; Shuyu Liu (Journal of Hazardous Materials, 2024)

Heat transfer performance study of Cu-ethanol/ethylene glycol/propylene glycol-water nanofluids in a wavy-walled tube heat exchanger - Liang Zhang; Jiabai Song; Pingping Qu; Shuangzhu Wang; Huimin Zhang; Hairui Wang; Hongfa Liu; Taiyan Lu (Journal of Environmental Chemical Engineering, 2024)

NIR-photocatalytic LDHB-mimetic CuS@ZnS nanoenzyme regulates arthritis microenvironment through lactate oxidation and hydrogen evolution - Dezhi Lu; Fan Wu; Kangming Chen; Wentao Li; Pingping Zhang; Yutong Hou; Yingze Su; Weixi Liu; Tianchang Wang; Yihao Liu; Chenglan Huang; Shuo Chen; et al. (Chemical Engineering Journal, 2024)

Effect of apple high-methoxyl pectin on heat-induced gelation of silver carp myofibrillar protein - Han Yu; Yunfeng Zhao; Runze Li; Xin Guo; Pingping Liu; Jian Zhang (Food Chemistry, 2024)

HH-A, a modified honokiol, protects against cerebral ischemia/reperfusion induced brain injury in rodent via Nrf2/HO-1 signaling pathways - Yuying Zhang; Pingping Zhang; Xin Zhang; Ye Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

N-S variations of crustal structure beneath the central Tarim Basin from joint inversion of receiver functions, ambient seismic noise surface wave dispersion, and magnetotelluric data - Miao Peng; Handong Tan; Changhong Lin; Shaoqian Hu; Pingping Wu; Lehong Xu; Chonglong Wang; Yifan Liu; Lihui Wang; Bohao Li (Tectonophysics, 2024)

Aromatic acids affect the performances of constructed rapid infiltration systems based on red mud and coke: Removal efficiency, electron transport, and metabolism - Shengtao Liu; Pingping Lu; Yunnan Zhang; Shu Gao; Xinjuan Li; Menglin Chen; Yuxiang Lu; Chengyuan Su (Journal of Environmental Chemical Engineering, 2024)

Mechanistic insights into the adsorption and extraction of rare earth ions using oxygen- and phosphorus-doped porous graphitic carbon nitride - Yiping Feng; Pingping Chen; Xingye Lian; Chenyi He; Chaoyu Zheng; Haijian Lu; Longyong Lin; Guoguang Liu; Yirong Deng (Journal of Environmental Chemical Engineering, 2024)

Identification and functional analysis of a CbSHR homolog in controlling adventitious root development in Catalpa bungei - Ziyuan Hao; Jingyi Liu; Yao Teng; Xinchang Wang; Peiyao Jiang; Weijie Si; Hongying Li; Fuqiang Yang; Pingping Guo; Jiawen Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Discussion on the development of offshore floating photovoltaic plants, emphasizing marine environmental protection - Sheng Wu; Nian Jiang; Shuai Zhang; Pingping Zhang; Peng Zhao; Yang Liu; Yanhui Wang (Frontiers in Marine Science, 2024)
The development of solar energy is one of the most effective means to deal with the environmental and energy crisis. The floating photovoltaic (PV) system is an attractive type because of its multiple advantages and has been well developed based on fresh water areas on land. This paper focuses on the expansion of this sector towards the ocean, offshore floating PV plants, which is the new growth point with huge potential for the future PV sector. For this new field, the technology readiness level is really low and research to understand the interaction between offshore floating PV plants and marine environment are proceeding. In this paper, we aim to discuss the technological feasibility of offshore floating PV plants as well as analyze potential impacts on the marine environment during the life cycle of PV from manufacturing until disposal.

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Assessing the impact of Chlorantraniliprole (CAP) pesticide stress on oilseed rape (Brassia campestris L.): Residue dynamics, enzyme activities, and metabolite profiling - Hui Zhang; Pingping Wang; Jiangfei Wang; Huijun Liu; Xiangning Chen (Pesticide Biochemistry and Physiology, 2024)

Physiological and biochemical responses of Leersia hexandra Swartz to nickel stress: Insights into antioxidant defense mechanisms and metal detoxification strategies - Mouyixing Chen; Pingping Jiang; Xuehong Zhang; Geoffrey I. Sunahara; Jie Liu; Guo Yu (Journal of Hazardous Materials, 2024)

Industrializable and pH-tolerant electropositive imidazolium chloride polymer for high-efficiency removal of perfluoroalkyl carboxylic acids from aqueous solution - Xiaohui Wei; Pingping Liu; Danyang Bai; Luyuan Zhang; Hongyan Mao; Wenjing Zhang; Tianqi Chen; Dan Yin; Tianhua Sun; Yanhao Zhang; Wenfen Zhang (Journal of Hazardous Materials, 2024)

You must separate: How perceived importance and language intensity promote waste separation - Yaojing Xu; Lin Zhang; Pingping Liu (Journal of Environmental Management, 2024)

Preparation and properties of films loaded with cellulose nanocrystals stabilized Thymus vulgaris essential oil Pickering emulsion based on modified tapioca starch/polyvinyl alcohol - Xin Guo; Xiaorui Wang; Yabo Wei; Pingping Liu; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2024)

N-nitrosodimethylamine exposure to zebrafish embryos/larvae causes cardiac and spinal developmental toxicity - Xiaoyi Liu; Jinge Song; Xiaotao Yan; Pingping Li; Jinhua Zhang; Bin Wang; Jing Si; Yong Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Accumulated Endogenous Abscisic Acid Contributes to the Cold Tolerance of Pre-planted Cultivated Tobacco - Qiansi Chen; Pingping Liu; Zefeng Li; Qingxia Zheng; Huina Zhou; Jinyan Liu; Peijian Cao; Ming Fang (Plant Molecular Biology Reporter, 2024)

Optimizing soil carbon content prediction performance by multi-band feature fusion based on visible near-infrared spectroscopy - Xueying Li; Pingping Fan; Huimin Qiu; Yan Liu (Journal of Soils and Sediments, 2024)

Adsorption of acetochlor-contaminated water systems using novel P-doped biochar: Effects, application, and mechanism - Wei Wang; Pingping Wang; Chi Wu; Lan Zhang; Liangang Mao; Lizhen Zhu; Hongyun Jiang; Yongquan Zheng; Xingang Liu (Chemosphere, 2024)

Changing soil available substrate primarily caused by fertilization management contributed more to soil respiration temperature sensitivity than microbial community thermal adaptation - Zhibin Guo; Chang-An Liu; Keke Hua; Daozhong Wang; Pingping Wu; Shuixia Wan; Chuanlong He; Linchuan Zhan; Ji Wu (Science of The Total Environment, 2024)

NtERF4 promotes the biosynthesis of chlorogenic acid and flavonoids by targeting PAL genes in Nicotiana tabacum - Shun He; Xin Xu; Qian Gao; Changjun Huang; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Haitao Huang; Jun Yang; Jianmin Zeng; Zhong Wang (Planta, 2024)

Magnetically separable Co0.6Fe2.4O4/MIL-101-NH2 adsorbent for Congo red efficient removal - Zhenhong Zhang; Yuye Zhong; Peng Sun; Pingping Zhao; Houbin Li; Xinghai Liu (Environmental Science and Pollution Research, 2024)

Full-scale upgrade activated sludge to continuous-flow aerobic granular sludge: Implementing microaerobic-aerobic configuration with internal separators - Cheng Yu; Kaijun Wang; Kaiyuan Zhang; Ruiyang Liu; Pingping Zheng (Water Research, 2024)

An inversion model of microplastics abundance based on satellite remote sensing: a case study in the Bohai Sea - Pingping Hong; Jingen Xiao; Hongtao Liu; Zhiguang Niu; Yini Ma; Qing Wang; Dianjun Zhang; Yongzheng Ma (Science of The Total Environment, 2024)

Investigation of the correlation between carbohydrate metabolization and pediocin sensitivity - Shanna Liu; Boqun Ding; Na Wang; Pingping Zhang; Ping Xiao (Biologia, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Bacterial wilt suppressive composts: Significance of rhizosphere microbiome - Jia Ding; Ning Wang; Pingping Liu; Baoju Liu; Yuelin Zhu; Jing Mao; Yue Wang; Xiaoyan Ding; Hefa Yang; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

The transcription factor NtERF13a enhances abiotic stress tolerance and phenylpropanoid compounds biosynthesis in tobacco - Zhong Wang; Jinchu Yang; Qian Gao; Shun He; Yongming Xu; Zhaopeng Luo; Pingping Liu; Mingzhu Wu; Xin Xu; Lanxin Ma; Zhan Zhang; Yongfeng Yang; et al. (Plant Science, 2023)

Identification and characterization of TMV-induced volatile signals in Nicotiana benthamiana: evidence for JA/ET defense pathway priming in congeneric neighbors via airborne (E)-2-octenal - Yi Hong; Qingxia Zheng; Lingtong Cheng; Pingping Liu; Guoyun Xu; Hui Zhang; Peijian Cao; Huina Zhou (Functional & Integrative Genomics, 2023)
Plants release a mixture of volatile compounds when subjects to environmental stress, allowing them to transmit information to neighboring plants. Here, we find that Nicotiana benthamiana plants infected with tobacco mosaic virus (TMV) induces defense responses in neighboring congeners. Analytical screening of volatiles from N. benthamiana at 7 days post inoculation (dpi) using an optimized SPME–GC–MS method showed that TMV triggers the release of several volatiles, such as (E)-2-octenal, 6-methyl-5-hepten-2-one, and geranylacetone. Exposure to (E)-2-octenal enhances the resistance of N. benthamiana plants to TMV and triggers the immune system with upregulation of pathogenesis-related genes, such as NbPR1a , NbPR1b , NbPR2 , and NbNPR1 , which are related to TMV resistance. Furthermore, (E)-2-octenal upregulates jasmonic acid (JA) that levels up to 400-fold in recipient N. benthamiana plants and significantly affects the expression pattern of key genes in the JA/ET signaling pathway, such as NbMYC2 , NbERF1 , and NbPDF1.2 , while the salicylic acid (SA) level is not significantly affected. Our results show for the first time that the volatile (E)-2-octenal primes the JA/ET pathway and then activates immune responses, ultimately leading to enhanced TMV resistance in adjacent N. benthamiana plants. These findings provide new insights into the role of airborne compounds in virus-induced interplant interactions.

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

A novel design and application of spatial data management platform for natural resources - Weijiang Kong; Tengji Wang; Lili Liu; Pingping Luo; Jianjun Cui; Ligang Wang; Xiankang Hua; Weili Duan; Feng Su (Journal of Cleaner Production, 2023)

Structural and functional diversity of the microbiome during the Phaeocystis globosa winter bloom in the southern Yellow Sea of China - Yue Xue; Qingshang Song; Dongmei Li; Xiyan Wang; Hui Liu; Cunchao Wu; Pingping Shen (International Biodeterioration & Biodegradation, 2023)

Immunomodulatory Mechanisms and Therapeutic Potential of Mesenchymal Stem Cells - Guoqiang Yang; Xuehui Fan; Yingchun Liu; Pingping Jie; Maryam Mazhar; Yong Liu; Nathupakorn Dechsupa; Li Wang (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cells (MSCs) are regarded as highly promising cells for allogeneic cell therapy, owing to their multipotent nature and ability to display potent and varied functions in different diseases. The functions of MSCs, including native immunomodulation, high self-renewal characteristic, and secretory and trophic properties, can be employed to improve the immune-modulatory functions in diseases. MSCs impact most immune cells by directly contacting and/or secreting positive microenvironmental factors to influence them. Previous studies have reported that the immunomodulatory role of MSCs is basically dependent on their secretion ability from MSCs. This review discusses the immunomodulatory capabilities of MSCs and the promising strategies to successfully improve the potential utilization of MSCs in clinical research. Graphical Abstract

Evaluation of cigarette smoke-induced oxidative stress and inflammation in BEAS-2B cells based on a lung microfluidic chip - Jingxian Xue; Zezhi Li; Xiang Li; Chenfeng Hua; Pingping Shang; Junwei Zhao; Kejian Liu; Fuwei Xie (Food and Chemical Toxicology, 2023)

Repeated Digestion by Earthworms on Tetracycline Degrading and Biological Responses in Tetracycline-Contaminated Sewage Sludge - Ping Liu; Taotao Zha; Si-Qi Xia; Pingping Sun; Yu-Feng Wu; Haitao Zhao; Ke Feng (Water, Air, & Soil Pollution, 2023)

Rice–fish coculture system enhances paddy soil fertility, bacterial network stability and keystone taxa diversity - Liping Ren; Pingping Liu; Fei Xu; Yanchao Gong; Xiangmei Zhai; Ming Zhou; Jiajia Wang; Zimeng Wang (Agriculture, Ecosystems & Environment, 2023)

Polycyclic aromatic hydrocarbons in the Chinese diet: contamination characteristics, indicator screening, and health risk assessment - Feifei Huang; Lei Zhang; Moqin Zhou; Jianwen Li; Qing Liu; Bo Wang; Ke Deng; Pingping Zhou; Yongning Wu (Food Additives & Contaminants: Part A, 2023)

How do morphological changes of caffeine hydrate influence caking - Pingping Cui; Yinggui Liu; Lihong Jia; Ling Zhou; Qiuxiang Yin (Journal of Food Engineering, 2023)

Integration of nitrogen-doped carbon dots onto active layer of forward osmosis membrane for highly efficient antibacteria and enhanced membrane performances - Wen-Sheng Zou; Pingping Wu; Bihua Xiao; Xia Chen; Weili Kong; Yaru Li; Zhaoming Liu; Yaqin Wang (Journal of Environmental Chemical Engineering, 2023)

Antibacterial castor oil-based waterborne polyurethane/gelatin films for packaging of strawberries - Yuye Zhong; Tao Zhang; Wenshuo Zhang; Guannan Wang; Zhenhong Zhang; Pingping Zhao; Xinghai Liu; Houbin Li (Food Packaging and Shelf Life, 2023)

Carbon amendment rather than nitrate fertilization dominated the reassembly of the total, denitrifying, and DNRA bacterial community in the anaerobic subsoil - Chen Chen; Pingping Liu; Yingjie Liu; Yuquan Wei; Ji Li; Guo-chun Ding (Journal of Soils and Sediments, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Using machine learning to quantify drivers of aerosol pollution trend in China from 2015 to 2022 - Yao Ji; Yunjiang Zhang; Diwen Liu; Kexin Zhang; Pingping Cai; Baizhen Zhu; Binqian Zhang; Jiukun Xian; Hongli Wang; Xinlei Ge (Applied Geochemistry, 2023)

Changes in bacterial diversity, co-occurrence pattern, and potential pathogens following digestate fertilization: Extending pathogen management to field for anaerobic digestion of livestock manure - Jingyang Gong; Baojun Liu; Pingping Liu; Lina Zhang; Chen Chen; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

The PER3rs772027021 SNP induces pigmentation phenotypes of dyschromatosis universalis hereditaria - Hongyu Chen; Pingping Yang; Dan Yang; Dongsheng Wang; Mao Lu; Yadong Li; Zhiqiang Zhong; Jing Zhang; Zhen Zeng; Zhi Liu; Xiaohua Zeng; Xu Jia; et al. (Journal of Molecular Medicine, 2023)

Effects of different levels of dietary chlorogenic acid supplementation on growth performance, intestinal integrity, and antioxidant status of broiler chickens at an early age - Wenhan Liu; Pingping Zha; Lili Guo; Yueping Chen; Yanmin Zhou (Animal Feed Science and Technology, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)

Spatial-temporal heterogeneity analysis of blue and green water resources for Poyang Lake basin, China - Mengyuan Liu; Pingping Zhang; Yanpeng Cai; Jianwen Chu; Yunliang Li; Xuan Wang; Chunhui Li; Qiang Liu (Journal of Hydrology, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

Occurrence and risk assessment of three chloroamide herbicides in water and soil environment in northeastern, eastern and southern China - Wei Wang; Yanli Man; Jun Xie; Zhi Zhang; Pingping Wang; Xingang Liu (Environmental Research, 2023)

Effects of LED spectrum on circadian rhythmic expression of clock genes and Aanat2 in the brain of juvenile European seabass (Dicentrarchus labrax) - He Ma; Songtao Liu; Pingping Wei; Fan Fei; Jilong Ren; Mingyun Dai; Zhen Ma; Ying Liu (Frontiers in Marine Science, 2023)
The circadian rhythm is a physiological phenomenon that occurs in various organisms with a cycle of about 24 hours. Light is one of the important environmental factors affecting biological rhythm. To clarify whether a shift in light spectrum can influence the circadian expression in fish brain, a total of 175 European seabasses [body weight: 32.5 ± 0.71) g; body length: (13.78 ± 0.35) cm] were exposed to white light (WL), red light (RL), yellow light (YL), green light (GL) or blue light (BL). After 50 days of exposure, circadian expressions of four core clock genes ( Clock, Bmal1, Per2, Cry1 ) and Aanat2 gene in brain were examined. The results showed that the temporal expression patterns of positive clock gens ( Clock and Bmal1 ) showed increases during the scotophase and decreases during the photophase, with peaks near the middle of the darkness. Clock gene expression showed a stable circadian rhythm (R 2 = 0.578-0.824, P =0.000- 0.027) in all light groups while Bmal1 showed circadian rhythm in WL, GL and RL, not in BL and YL. Daily expression patterns of the negative clock genes oscillated in the opposite phase from the positive clock genes, showing increasing mRNA levels during the light, decreases during the dark, and peaks near the shift from night to day, except Per2 in RL and Cry1 in BL. Compared with WL, the acrophases of Clock and Bmal1 were delayed under all light treatments (BL: + 3.7h, +6.73h; RL: +2.4h,+1.35h; YL: + 4.94h, 2.00h; GL: +0.05, +0.16h). Cry1 showed advanced acrophase under all light treatments (BL: -10.74 h, GL: -3.81 h, RL: -3.93 h, YL: -7.56 h) but Per2 showed delayed acrophase in all light treatments (GL: +0.86 h, RL: +10.35 h, YL: +9.62 h), except in BL (-0.43 h). The acrophase of Aanat2 was advanced by all monochromatic light, the Aanat2 level was significantly increased in RL compared with other light treatment. Therefore, the results indicate that RL may regulate the expression of Aanat2 gene by affecting the expression of clock gene in fish brain. Spectrum can affect the biological clock system of fish, and unreasonable spectrum may disturb the rhythm of gene expression of biological clock of fish. Under the irradiation of light spectrum, some clock genes still maintain obvious circadian oscillation, while the rhythm of some clock genes is not obvious and may be destroyed. Our findings suggest a primary role of light spectrum information to the fish brain circadian system.

Cytotoxicity and pro-inflammatory effect of polystyrene nano-plastic and micro-plastic on RAW264.7 cells - Xiaoxia Wang; Xiao-Min Ren; Huan He; Fan Li; Kunqian Liu; Fenqing Zhao; Huixiang Hu; Pingping Zhang; Bin Huang; Xuejun Pan (Toxicology, 2023)

Transcription factor NtWRKY33a modulates the biosynthesis of polyphenols by targeting NtMYB4 and NtHCT genes in tobacco - Zhong Wang; Lanxin Ma; Pingping Liu; Zhaopeng Luo; Zefeng Li; Mingzhu Wu; Xin Xu; Wenxuan Pu; Pingjun Huang; Jun Yang (Plant Science, 2023)

A global survey of organophosphate esters and their metabolites in milk: Occurrence and dietary intake via milk consumption - Shunying Yao; Zhixiong Shi; Pei Cao; Lei Zhang; Yu Tang; Pingping Zhou; Zhaoping Liu (Journal of Hazardous Materials, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

What happens to gut microorganisms and potential repair mechanisms when meet heavy metal(loid)s - Xiaoyi Liu; Jinhua Zhang; Jing Si; Pingping Li; Haining Gao; Weikun Li; Yong Chen (Environmental Pollution, 2023)

Application of an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands: Mechanisms of pollutants removal and greenhouse gases reduction - Xiuzheng Fu; Zhengda Yu; Fanlong Kong; Pingping Duan; Fanyi Li; Lingzhu Zhang; Zhongying Liu; Yuqian Cui (Bioresource Technology, 2023)

Assessment of heavy metals contamination and human health risk assessment of the commonly consumed medicinal herbs in China - Haiping Liu; Jianfeng Tang; Tongjun Chen; Pingping Zhu; Dongdong Sun; Weiyun Wang (Environmental Science and Pollution Research, 2023)

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Application of resistivity measurement to stability evaluation for loess slopes - Bin Zhang; Li Feng; Maosheng Zhang; Pingping Sun; Tonglu Li; Hao Liu (Landslides, 2022)

BiPO4-coated carbon microtube electrodes: preparation and characterization of their properties and electrocatalytic degradation of methylene blue - Wenli Qin; Zefei Chen; Xueya Liu; Xinyi Zhang; Manqing Ai; Pingping Zhang; Ying Ye; Zengling Ma (Environmental Science and Pollution Research, 2022)

Spatial Distribution and Assessment of the Human Health Risks of Heavy Metals in a Retired Pharmaceutical Industrial Area, Southwest China - Shiyu Wang; Zhaohui Ma; Guoren Yue; Haolan Wu; Pingping Wang; Ling Zhu; Cunzhen Liang; Chengcheng Xie; Shuo Wang; Wentao Jiao; Bendong Zou; Baoxian Liu (Bulletin of Environmental Contamination and Toxicology, 2022)

Identification and Characterization of microRNAs in the Gonads of Litopenaeus vannamei Using High-Throughput Sequencing - Wei Li; Pingping He; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Li Zhang; Bin Zhang; Yusi Zheng; Xin Li; Qingsong He; Longcheng Liu; Chang Yuan; et al. (Fishes, 2022)
Although the expression of miRNAs has been widely applied to investigate on gonads, the role of miRNAs in the gonadal development of white Pacific shrimp (Litopenaeus vannamei) remains unknown. In this study, we performed high-throughput sequencing to identify the sex-related microRNAs (miRNAs) that elucidated the regulatory mechanisms on the gonadal differentiation of L. vannamei. We obtained a total of 29,671,557 and 28,526,942 raw reads from the ovaries and testes library, respectively. We then mapped 26,365,828 (92.73%) of the ovarian clean sequences and 23,694,294 (85.65%) of the testicular clean sequences for a transcriptome reference sequence of L. vannamei. After blasting the miRNA sequences against the miRBase database, we identified 153 significantly differentially expressed miRNAs between the ovaries and testes. To confirm the high-throughput sequencing results, we used a reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) to verify the expression patterns of the seven most differentially expressed miRNAs (i.e., novel_mir23, miR-92b-3p_3, miR-12-5p_2, novel_mir67, miR-279_1, let-7-5p_6, miR-263a-5p_1). According to the results of RT-qPCR, most of the miRNAs were expressed consistently with the high-throughput sequencing results. In addition, the target genes significantly enriched several Kyoto Encyclopedia of Genes and Genome (KEGG) pathways that were closely related to gonadal differentiation and development, including extracellular matrix–receptor interaction, Hedgehog signaling pathway, protein digestion and absorption and cell adhesion molecules (CAMs). This study revealed the first miRNAs sequencing of L. vannamei gonads. We identified sex-related differentially expressed miRNAs and KEGG pathways, which will be helpful to facilitate future research into the regulatory mechanism on the gonadal differentiation of L. vannamei.

rtcisE2F promotes the self-renewal and metastasis of liver tumor-initiating cells via N6-methyladenosine-dependent E2F3/E2F6 mRNA stability - Zhenzhen Chen; Lan Huang; Kaili Wang; Lulu Zhang; Xiang Zhong; Zhongyi Yan; Benyu Liu; Pingping Zhu (Science China Life Sciences, 2022)

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Pathways of cadmium fluxes in the root of the hyperaccumulator Celosia argentea Linn. - Pingping Jiang; Yingyi Zheng; Jie Liu; Guo Yu; Fanyu Lin (Environmental Science and Pollution Research, 2022)

Brain functional specialization and cooperation in Parkinson’s disease - Jinmei Sun; Xiaoran Gao; Qiang Hua; Rongrong Du; Pingping Liu; Tingting Liu; Jinying Yang; Bensheng Qiu; Gong-Jun Ji; Panpan Hu; Kai Wang (Brain Imaging and Behavior, 2022)

Selection Signatures of Pacific White Shrimp Litopenaeus vannamei Revealed by Whole-Genome Resequencing Analysis - Hao Wang; Mingxuan Teng; Pingping Liu; Mingyang Zhao; Shi Wang; Jingjie Hu; Zhenmin Bao; Qifan Zeng (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is among the top aquatic species of commercial importance around the world. Over the last four decades, the breeding works of L. vannamei have been carried out intensively and have generated multiple strains with improved production and performance traits. However, signatures of domestication and artificial selection across the L. vannamei genome remain largely unexplored. In the present study, we conducted whole genomic resequencing of 180 Pacific white shrimps from two artificially selective breeds and four market-leading companies. A total of 37 million single nucleotide polymorphisms (SNPs) were identified with an average density of 22.5 SNPs/Kb across the genome. Ancestry estimation, principal component analysis, and phylogenetic inference have all revealed the obvious stratifications among the six breeds. We evaluated the linkage disequilibrium (LD) decay in each breed and identified the genetic variations driven by selection. Pairwise comparison of the fixation index ( F st ) and nucleotide diversity (θ π ) has allowed for mining the genomic regions under selective sweep in each breed. The functional enrichment analysis revealed that genes within these regions are mainly involved in the cellular macromolecule metabolic process, proteolysis, structural molecule activity, structure of the constituent ribosome, and responses to stimulus. The genome-wide SNP datasets provide valuable information for germplasm resources assessment and genome-assisted breeding of Pacific white shrimps, and also shed light on the genetic effects and genomic signatures of selective breeding.

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Transcriptional Responses of Flavin-Containing Monooxygenase Genes in Scallops Exposed to PST-Producing Dinoflagellates Implying Their Involvements in Detoxification - Lingling Kong; Pingping Liu; Moli Li; Huizhen Wang; Jiaoxia Shi; Jingjie Hu; Yueru Li; Xiaoli Hu (Frontiers in Marine Science, 2021)
Flavin-containing monooxygenase (FMO) is one of the most prominent xenobiotic metabolic enzymes. It can catalyze the conversion of heteroatom-containing chemicals to polar, readily excretable metabolites and is considered an efficient detoxification system for xenobiotics. Bivalves can accumulate paralytic shellfish toxins (PSTs) produced by dinoflagellates, especially during outbreaks of harmful algal blooms. Exploring FMO genes in bivalves may contribute to a better understanding of the adaptation of these species and the mechanisms of PSTs bioavailability. Therefore, through genome screening, we examined the expansion of FMO genes in two scallops ( Patinopecten yessoensis and Chlamys farreri ) and found a new subfamily (FMO_like). Our expression analyses revealed that, in both scallops, members of the FMO_N-oxide and FMO_like subfamilies were mainly expressed from the D-stage larvae to juveniles, whereas the FMO_GS-OX subfamily genes were mainly expressed at and prior to the trochophore stage. In adult organs, higher expressions of FMO s were observed in the kidney and hepatopancreas than in other organs. After exposure to PST-producing algae, expression changes in FMO s occurred in hepatopancreas and kidney of both scallops, with more members being up-regulated in hepatopancreas than in kidney for Alexandrium catenella exposure, while more up-regulated FMO s were found in kidney than in hepatopancreas of C. farreri exposed to A. minutum . Our findings suggest the adaptive functional diversity of scallop FMO genes in coping with the toxicity of PST-producing algae.

A Genome-Wide Association Study Identifies Candidate Genes Associated With Shell Color in Bay Scallop Argopecten irradians irradians - Xinghai Zhu; Junhao Zhang; Xiujiang Hou; Pingping Liu; Jia Lv; Qiang Xing; Xiaoting Huang; Jingjie Hu; Zhenmin Bao (Frontiers in Marine Science, 2021)
Molluscan shell color has consistently drawn attention for its abundant diversity and commercial use in shellfish breeding projects. Recently, two new strains of bay scallop ( Argopecten irradians irradians ) with different shell colors as marked phenotypic traits have been artificially bred to improve their economic values; however, the inheritance mechanism of their shell pigmentation is still unclear. In this study, a genome-wide association study (GWAS) was conducted to determine the genetic basis of shell color in bay scallops utilizing 29,036 high-quality single-nucleotide polymorphisms (SNPs) derived from 80 purple-red (PP) and 80 black-brown (BP) shell color individuals. The result of the GWAS showed that 469 SNPs ( p <1.72E−6) significantly associated with shell color were mainly distributed in chromosome 7. The top three SNPs (i.e., chr7-12764003, chr7-13213864, and chr7-11899306) are located in the genic region of G-protein-coupled receptor-like 101 ( GRL101 ), polyketide synthase 1 ( PKS1 ), and phosphoinositide phospholipase C ( PLC1 ), which have been widely reported to be involved in pigmentation. Successfully, the top three SNPs were verified in another non-breeding bay scallop population. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses obtained 38 GO terms covering 297 genes and aggregating pathways involving 252 annotated genes. Specifically, the expression profiles of the top three identified candidate genes were detected in mantles of PP and BP individuals by real-time quantitative reverse transcription PCR. The significantly higher expression levels of GRL101 (6.43-fold) and PLC1 (6.48-fold) in PP, and PKS1 (12.02-fold) in BP implied that GRL101 and PLC1 potentially functioned in PP shell coloration, and black pigmentation in BP might be principally regulated by PKS1 . Our data provide valuable information for deciphering the phenotype differences of shell color in the bay scallop.

Occurrence of 3- and 2-monochloropropanediol esters in infant formulas in China and exposure assessment - Xia Cui; Lei Zhang; Dajin Yang; Jianwen Li; Qing Liu; Haixia Sui; Zhaoping Liu; Pingping Zhou (Food Additives & Contaminants: Part A, 2021)

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1) - Ming Li; Ling Xue; Weibin Xu; Pingping Liu; Feng Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The apoptosis of GCs was facilitated by NE. Wilms tumor 1 (WT1) was found to be significantly downregulated in GCs after NE treatment, and overexpression of WT1 repressed apoptosis in rat GCs induced by NE. rno-miR-128-3p was found to be significantly enhanced by NE in GCs, and inhibition of rno-miR-128-3p repressed apoptosis in rat GCs induced by NE. Mechanistically, rno-miR-128-3p interacted with WT1 and repressed its expression. In summary, inhibition of rno-miR-128-3p may enhance WT1 expression, and then repress NE-induced apoptosis in rat GCs. Our research may provide a new insight for the improvement of ovarian follicular development.

Bioavailability of heavy metals bounded to PM2.5 in Xi’an, China: seasonal variation and health risk assessment - Tiantian Wu; Pingping Liu; Xintian He; Hongmei Xu; Zhenxing Shen (Environmental Science and Pollution Research, 2021)

Causal associations of waist circumference and waist-to-hip ratio with type II diabetes mellitus: new evidence from Mendelian randomization - Kexin Li; Tianyu Feng; Lijuan Wang; Yang Chen; Pingping Zheng; Pan Pan; Min Wang; Isaac T. S. Binnay; Yingshuang Wang; Ruiyu Chai; Siyu Liu; Bo Li; et al. (Molecular Genetics and Genomics, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The global research trend on cadmium in freshwater: a bibliometric review - Muhammad Irfan; Xianhua Liu; Khalid Hussain; Suraya Mushtaq; Jonnathan Cabrera; Pingping Zhang (Environmental Science and Pollution Research, 2021)

Molecular Cloning, Expression and Characterization of Peroxisome Proliferators-Activated Receptors Gamma in the Sea Urchin (Strongylocentrotus intermedius) - Zijiao Quan; Lingshu Han; Yue Cao; Pingping Gao; Xiaoyu Liu; Yaqing Chang; Jun Ding (Journal of Ocean University of China, 2021)

Omics resources and omics-enabled approaches for achieving high productivity and improved quality in pea (Pisum sativum L.) - Arun K. Pandey; Diego Rubiales; Yonggang Wang; Pingping Fang; Ting Sun; Na Liu; Pei Xu (Theoretical and Applied Genetics, 2021)

Development and application of a comparative risk assessment method for ranking chemical hazards in food - Ying Li; Guoxin Liang; Lei Zhang; Zhaoping Liu; Dajin Yang; Jianwen Li; Guiju Sun; Pingping Zhou (Food Additives & Contaminants: Part A, 2021)

Dietary exposure of general Chinese population to fatty acid esters of 3-monochloropropane-1, 2-diol (3-MCPD) from edible oils and oil-containing foods - Xia Cui; Lei Zhang; Pingping Zhou; Zhaoping Liu; Sai Fan; Dajin Yang; Jianwen Li; Qing Liu (Food Additives & Contaminants: Part A, 2021)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

Methylomonas rhizoryzae sp. nov., a type I methanotroph isolated from the rhizosphere soil of rice - Pingping Zhu; Minggen Cheng; Dongmei Pei; Yongchuang Liu; Xin Yan (Antonie van Leeuwenhoek, 2020)

Perfluoroalkyl substances in the Lingang hybrid constructed wetland, Tianjin, China: occurrence, distribution characteristics, and ecological risks - Ziang Chen; Gengbo Ren; Xiaodong Ma; Ye Ding; Yunmin Hui; Pingping Qin; Zhuoqi Xu; Xiujun Gu; Fang Yuan; Yanhai Liu (Environmental Science and Pollution Research, 2020)

Interaction of Mn and Cd during their uptake in Celosia argentea differs between hydroponic and soil systems - Jie Liu; Guo Yu; Pingping Jiang; Xingfeng Zhang; Dejia Meng; Zhe Chen; Alan J. M. Baker; Rongliang Qiu (Plant and Soil, 2020)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Compensation effects of coated cysteamine on meat quality, amino acid composition, fatty acid composition, mineral content in dorsal muscle and serum biochemical indices in finishing pigs offered reduced trace minerals diet - Miaomiao Bai; Hongnan Liu; Kang Xu; Xiaofeng Zhang; Baichuan Deng; Chengquan Tan; Jinping Deng; Pingping Bing; Yulong Yin (Science China Life Sciences, 2019)

Acid-extractable heavy metals in PM2.5 over Xi’an, China: seasonal distribution and meteorological influence - Pingping Liu; Yiling Zhang; Tiantian Wu; Zhenxing Shen; Hongmei Xu (Environmental Science and Pollution Research, 2019)

Reactive oxygen species induced by personal exposure to fine particulate matter emitted from solid fuel combustion in rural Guanzhong Basin, northwestern China - Yaqi Li; Hongmei Xu; Kailai He; Jinhui Wang; Zhi Ning; Qiyuan Wang; Nan Li; Zhenxing Shen; Pingping Liu; Jian Sun; Xinyi Niu; Yongxiao Cao; et al. (Air Quality, Atmosphere & Health, 2019)

Identification and characterization of protein phosphorylation in the soluble protein fraction of scallop (Chlamys farreri) byssus - Lixia Zhang; Xiaokang Zhang; Yujie Wang; Pingping Xu; Zhenli Diao; Weizhi Liu; Wenhua Xu (Molecular Biology Reports, 2019)

Early Cretaceous volcanic and sub-volcanic rocks in the Erlian Basin and adjacent areas, Northeast China: new geochemistry, geochronology and zircon Hf isotope constraints on petrogenesis and tectonic setting - Jianzhou Tang; Zhicheng Zhang; Zejia Ji; Yan Chen; Ke Li; Yang Jinfu; Pingping Liu (International Geology Review, 2019)

DNA methylation of CRB3 is a prognostic biomarker in clear cell renal cell carcinoma - Pingping Li; Jie Liu; Juan Li; Peijun Liu (Molecular Biology Reports, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Is phosphorus a limiting factor to regulate the growth of phytoplankton in Daya Bay, northern South China Sea: a mesocosm experiment - Xingyu Song; Meiting Tan; Ge Xu; Xinying Su; Jihua Liu; Gaungyan Ni; Yao Li; Yehui Tan; Liangmin Huang; Pingping Shen; Gang Li (Ecotoxicology, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Use of multiple isotopes to evaluate the impact of mariculture on nutrient dynamics in coastal groundwater - Kang Pingping; Liu Peng; Wang Fuqiang (Environmental Science and Pollution Research, 2019)

Evolutionary and functional analyses of the 2-oxoglutarate-dependent dioxygenase genes involved in the flavonoid biosynthesis pathway in tobacco - Zhong Wang; Shanshan Wang; Mingzhu Wu; Zefeng Li; Pingping Liu; Feng Li; Qiansi Chen; Aiguo Yang; Jun Yang (Planta, 2019)

Foliage application of nitrogen has less influence on soil microbial biomass and community composition than soil application of nitrogen - Xingran Huang; Yanfei Liu; Yiyong Li; Pingping Guo; Xiong Fang; Zhigang Yi (Journal of Soils and Sediments, 2019)

Assessment of heavy metal characteristics and health risks associated with PM2.5 in Xi’an, the largest city in northwestern China - Pingping Liu; Huarui Ren; Hongmei Xu; Yali Lei; Zhenxing Shen (Air Quality, Atmosphere & Health, 2018)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Improving photoelectrochemical reduction of Cr(VI) ions by building α-Fe2O3/TiO2 electrode - Pingping Wang; Faqin Dong; Mingxue Liu; Huichao He; Tingting Huo; Lei Zhou; Wei Zhang (Environmental Science and Pollution Research, 2018)

Chasing ghosts: allopolyploid origin of Oxyria sinensis (Polygonaceae) from its only diploid congener and an unknown ancestor - Xin Luo; Quanjun Hu; Pingping Zhou; Dan Zhang; Qian Wang; Richard J. Abbott; Jianquan Liu (Molecular Ecology, 2017)
Reconstructing the origin of a polyploid species is particularly challenging when an ancestor has become extinct. Under such circumstances, the extinct donor of a genome found in the polyploid may be treated as a ‘ghost’ species in that its prior existence is recognized through the presence of its genome in the polyploid. In this study, we aimed to determine the polyploid origin of Oxyria sinensis (2 n = 40) for which only one congeneric species is known, that is diploid O. digyna (2 n = 14). Genomic in situ hybridization (GISH), transcriptome, phylogenetic and demographic analyses, and ecological niche modelling were conducted for this purpose. GISH revealed that O. sinensis comprised 14 chromosomes from O. digyna and 26 chromosomes from an unknown ancestor. Transcriptome analysis indicated that following divergence from O. digyna , involving genome duplication around 12 million years ago (Ma), a second genome duplication occurred approximately 6 Ma to give rise to O. sinensis . Oxyria sinensis was shown to contain homologous gene sequences divergent from those present in O. digyna in addition to a set that clustered with those in O. digyna . Coalescent simulations indicated that O. sinensis expanded its distribution approximately 6–7 Ma, possibly following the second polyploidization event, whereas O. digyna expanded its range much later. It was also indicated that the distributions of both species contracted and re‐expanded during the Pleistocene climatic oscillations. Ecological niche modelling similarly suggested that both species experienced changes in their distributional ranges in response to Quaternary climatic changes. The extinction of the unknown ‘ghost’ tetraploid species implicated in the origin of O. sinensis could have resulted from superior adaptation of O. sinensis to repeated climatic changes in the region where it now occurs.

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Sorption of Sulfadiazine, Norfloxacin, Metronidazole, and Tetracycline by Granular Activated Carbon: Kinetics, Mechanisms, and Isotherms - Pingping Liu; Qiaorui Wang; Chunli Zheng; Chi He (Water, Air, & Soil Pollution, 2017)

Differentiation of bone marrow stromal cells into schwann-like cells using dihydrotestosterone combined with a classical induction method - Xiaofan Yang; Jianghai Chen; Pingping Xue; Ranran Liu; Wei Ji; Xiaocheng Lu; Xin Liu; Zhenbing Chen (Biotechnology Letters, 2017)

Degradation of cyflumetofen and formation of its main metabolites in soils and water/sediment systems - Pingping Wang; Minmin Li; Xingang Liu; Jun Xu; Fengshou Dong; Xiaohu Wu; Yongquan Zheng (Environmental Science and Pollution Research, 2016)

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

Application of SPME-GC/MS to Study the Sorption of Organophosphate Esters on Peat Soil - Chunli Zheng; Shanshan Feng; Qiaorui Wang; Pingping Liu; Zhengxing Shen; Hongxia Liu; Liu Yang (Water, Air, & Soil Pollution, 2016)

Transplantation of mesenchymal stem cells improves type 1 diabetes mellitus - Lisha Li; Furong Li; Feng Gao; Yali Yang; Yuanyuan Liu; Pingping Guo; Yulin Li (Cell and Tissue Research, 2016)

Composition and distribution of planktonic ciliates in the southern South China Sea during late summer: Comparison between surface and 75 m deep layer - Huaxue Liu; Pingping Shen; Chunhou Li; Zuozhi Chen; Zhanhui Qi; Honghui Huang (Journal of Ocean University of China, 2016)

A novel l-asparaginase from Aquabacterium sp. A7-Y with self-cleavage activation - Zhibin Sun; Ding Li; Pingping Liu; Wenhui Wang; Kai Ji; Yan Huang; Zhongli Cui (Antonie van Leeuwenhoek, 2016)

Transcriptomic Analyses Reveal Novel Genes with Sexually Dimorphic Expression in Yellow Catfish (Pelteobagrus fulvidraco) Brain - Jianguo Lu; Min Zheng; Jiajia Zheng; Jian Liu; Yongzhuang Liu; Lina Peng; Pingping Wang; Xiaofeng Zhang; Qiushi Wang; Peixian Luan; Shahid Mahbooband; Xiaowen Sun (Marine Biotechnology, 2015)

Cloning and functional analyses of pepper CaRKNR involved in Meloidogyne incognita resistance - Zhenchuan Mao; Pingping Zhu; Feng Liu; Yonghong Huang; Jian Ling; Guohua Chen; Yuhong Yang; Dongxin Feng; Bingyan Xie (Euphytica, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Review of arsenic speciation, toxicity and metabolism in microalgae - Ya Wang; Shu Wang; Pingping Xu; Cong Liu; Misha Liu; Yulan Wang; Changhai Wang; Chunhua Zhang; Ying Ge (Reviews in Environmental Science and Bio/Technology, 2015)

BTG3 upregulation induces cell apoptosis and suppresses invasion in esophageal adenocarcinoma - Yuwen Du; Pingping Liu; Wenqiao Zang; Yuanyuan Wang; Xiaonan Chen; Min Li; Guoqiang Zhao (Molecular and Cellular Biochemistry, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Isolation and characterization of a proteinaceous α-amylase inhibitor AAI-CC5 from Streptomyces sp. CC5, and its gene cloning and expression - Zhibin Sun; Weihao Lu; Pingping Liu; Hui Wang; Yan Huang; Yuguo Zhao; Yi Kong; Zhongli Cui (Antonie van Leeuwenhoek, 2015)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)

NIPA2 located in 15q11.2 is mutated in patients with childhood absence epilepsy - Yuwu Jiang; Yuehua Zhang; Pingping Zhang; Tian Sang; Feng Zhang; Taoyun Ji; Qionghui Huang; Han Xie; Renqian Du; Bin Cai; Haijuan Zhao; Jingmin Wang; et al. (Human Genetics, 2012)

Longitudinal patterns of spring-intermonsoon phytoplankton biomass, species compositions and size structure in the Bay of Bengal - Gang Li; Zhixin Ke; Qiang Lin; Guangyan Ni; Pingping Shen; Huaxue Liu; Jianqiang Yin; Kaizhi Li; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2012)

Geochronologic-petrochemical studies of the Hongshishan mafic–ultramafic intrusion, Beishan area, Xinjiang (NW China): petrogenesis and tectonic implications - Benxun Su; Kezhang Qin; Patrick Asamoah Sakyi; Dongmei Tang; Pingping Liu; Sanjeewa P.K. Malaviarachchi; Qinghua Xiao; He Sun (International Geology Review, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)

Olivine compositional mapping of mafic-ultramafic complexes in eastern Xinjiang (NW China): Implications for Cu-Ni mineralization and tectonic dynamics - Benxun Su; Kezhang Qin; He Sun; Dongmei Tang; Qinghua Xiao; Pingping Liu; Patrick Asamoah Sakyi (Journal of Earth Science, 2012)

Formation of melt pocket in mantle peridotite xenolith from western Qinling, Central China: Partial melting and metasomatism - Benxun Su; Hongfu Zhang; Patrick Asamoah Sakyi; Kezhang Qin; Pingping Liu; Jifeng Ying; Yanjie Tang; Sanjeewa P. K. Malaviarachchi; Yan Xiao; Xinmiao Zhao; Qian Mao; Yuguang Ma (Journal of Earth Science, 2010)

Lipase-catalyzed selective synthesis of monolauroyl maltose using continuous stirred tank reactor - Qiaoyu Liu; Chengsheng Jia; Jin M. Kim; Pingping Jiang; Xiaoming Zhang; Biao Feng; Shiying Xu (Biotechnology Letters, 2008)

D-Galactose-caused life shortening in Drosophila melanogaster and Musca domestica is associated with oxidative stress - Xu Cui; Luning Wang; Pingping Zuo; Zhitao Han; Zhengyu Fang; Wenbin Li; Jiankang Liu (Biogerontology, 2004)

Effects of turbulent dispersion of atmospheric balance motions of planetary boundary layer - Liu Shikuo; Huang Wei; Rong Pingping (Advances in Atmospheric Sciences, 1992)